Kesiapan Guru Dalam Menggunakan eknologi Informasi Untuk Pembelajaran Kurikulum 2013 Pada SMP Negeri Kota Palembang - Deasy Arianty; Darius Antoni; Muhammad Akbar (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
The 2013 curriculum is a new curriculum issued by the Ministry of Education and Culture of the Republic of Indonesia. The 2013 curriculum itself is a curriculum that prioritizes understanding, skills, and character education, where students are required to understand the material, be active in the discussion and presentation process and have high manners and discipline. This curriculum officially replaces the Education Unit Level Curriculum which has been implemented since 2006. However, there are still many teachers who find it difficult to apply this approach in teaching and using learning media, one of which is information technology. The results of the research explanation can be revealed that the readiness of teachers to use information technology in the 2013 curriculum is around 79% ready and categorized as high, in this case technology and information are not only used in the computer field but can also be used as learning media in the 2013 curriculum-scientific approach , without eliminating the essence of the basic concepts of the 2013 curriculum.